Children with Learning Disabilities – Teaching Effective Coping Strategies - BANSAL, SNEH (THE PRIMARY TEACHER, 2014)
In India, disability is still viewed in terms of a “misfortune” with a ‘better dead than disabled’ approach; the idea being that it is not possible for children with disability to enjoy and lead a good quality of life. The parents of children with disabilities develop ‘chronic sorrow’ characterised by periodic recurrence of grief, shame, shock and pain. They are overwhelmed by feelings of glumness, resentment, and humiliation. Rejection, projection of blame, guilt, pain, withdrawal and acceptance are some of the usual parental reactions. Some parents also experience helplessness, feelings of inadequacy, anger, shock and guilt, whereas others go through periods of disbelief, depression and self-blame. The siblings also experience feelings of guilt, shame and embarrassment (Frude, 1992)